A Light Field Imaging Based Measuring Method for Blast Furnace Burden Distribution⁎. Issue 21 (2018) - Xu, Tianxiang; Jiang, Zhaohui; Gui, Weihua
Abstract: Accurate height and distribution of blast furnace burden is essential to improve coke-ore ratio, improve gas flow and reduce CO2 emission. However, conventional burden distribution measure method by mechanical sounding rod can only measure 2 or 3 fixed discontinues burden height information. This article uses a light field imaging system to estimate blast furnace burden distribution. At first, the light field camera is used to obtain 4D image of the burden surface, light position and angle information is utilized to refocus to obtain focal stack images. Then the depth of burden surface is obtained by finding out the refocused image to target depth based on laplacian operator. At last, the whole burden surface is reconstructed in Csharp/emgu platform to extract burden surface distribution and radial burden distribution.